2017
DOI: 10.1016/j.copbio.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans and its bacterial diet as a model for systems-level understanding of host–microbiota interactions

Abstract: Resident microbes of the human body, particularly the gut microbiota, provide essential functions for the host, and, therefore, have important roles in human health as well as mitigating disease. It is difficult to study the mechanisms by which the microbiota affect human health, especially at a systems-level, due to heterogeneity of human genomes, the complexity and heterogeneity of the gut microbiota, the challenge of growing these bacteria in the laboratory, and the lack of bacterial genetics in most microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 56 publications
0
75
0
Order By: Relevance
“…Moreover, metabolic interactions among members of the microbiota help maintain community structure, thereby preventing pathogen invasion or other dysbioses (3). C. elegans is a useful model host for microbiome studies, particularly in relation to development and host-pathogen interactions (9,10). In this study, we developed a model of metabolic microbe-host interactions and directly demonstrated that colonization with heterologous bacteria enables C. elegans to digest and incorporate carbon from 5 previously indigestible long-chain carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, metabolic interactions among members of the microbiota help maintain community structure, thereby preventing pathogen invasion or other dysbioses (3). C. elegans is a useful model host for microbiome studies, particularly in relation to development and host-pathogen interactions (9,10). In this study, we developed a model of metabolic microbe-host interactions and directly demonstrated that colonization with heterologous bacteria enables C. elegans to digest and incorporate carbon from 5 previously indigestible long-chain carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we assembled a functional microbiome in a simple animal gut to allow host utilization of a complex carbohydrate source. We used the nematode Caenorhabditis elegans as 20 the animal host because it has been extensively used as a model system to elucidate mechanisms of interaction between prokaryotes and their hosts (9,10). Specifically, we colonized C. elegans with cellulolytic bacteria that break down cellulose in the gut, such that the released glucose is available as a nutrient for both C. elegans itself and the colonizing bacteria.…”
mentioning
confidence: 99%
“…Although NO molecules have high permeability through the membranes of lactobacillus and intracellular structures due to their small sizes. This result indicates that bacterial NO is generally beneficial to worms [70] indicates NO Promotes heat – tolerance (stress tolerance) in C. elegans [7173]. …”
Section: Discussionmentioning
confidence: 99%
“…However, whether bacterial metabolites directly influence neuronal degeneration and their mechanisms of action is largely unknown. The bacterivore nematode C. elegans continues to provide an excellent model to study the relationship between bacteria and host [12]. Both the animal and its bacterial diet are genetically tractable making them suitable for individual gene and large-scale mutation analysis.…”
Section: Introductionmentioning
confidence: 99%